Nain, Häuserreiche von hinten gesehen : [ca. 1901] - Schmitt, Christian, 1868-1933. (2001)
Black and white photograph of a rear view of houses in Nain, with a group of Inuit in the foreground, circa 1901. Black and white photograph of a rear view of houses in Nain, with a group of Inuit in the foreground, circa 1901.